2016
DOI: 10.1002/2015jd024686
|View full text |Cite
|
Sign up to set email alerts
|

Retrievals of ice cloud microphysical properties of deep convective systems using radar measurements

Abstract: This study presents newly developed algorithms for retrieving ice cloud microphysical properties (ice water content (IWC) and median mass diameter (D m )) for the stratiform rain and thick anvil regions of deep convective systems (DCSs) using Next Generation Radar (NEXRAD) reflectivity and empirical relationships from aircraft in situ measurements. A typical DCS case (20 May 2011) during the Midlatitude Continental Convective Clouds Experiment (MC3E) is selected as an example to demonstrate the 4-D retrievals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…This is not true for the IWC retrievals using K dp (Aydin & Tang, ; Lu et al, ; Ryzhkov & Zrnic, ). Here the IWCs and IWPs retrieved from two algorithms (Lu et al, ; Tian et al, ) are compared for the PS case in order to help quantify the uncertainties of the Z e retrievals.…”
Section: Discussion Of Uncertainties In Iwc Retrieval Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not true for the IWC retrievals using K dp (Aydin & Tang, ; Lu et al, ; Ryzhkov & Zrnic, ). Here the IWCs and IWPs retrieved from two algorithms (Lu et al, ; Tian et al, ) are compared for the PS case in order to help quantify the uncertainties of the Z e retrievals.…”
Section: Discussion Of Uncertainties In Iwc Retrieval Algorithmmentioning
confidence: 99%
“…It was further evaluated with aircraft‐measured IWC values from two field campaigns, the Mid‐latitude Continental Convective Clouds Experiment (MC3E) and the Bow Echo and Mesoscale Convective Vortices Experiment (BAMEX). Compared with the aircraft in situ measurements, the uncertainty of IWC retrievals is ~40% during the MC3E, while a positive bias is found during the BAMEX around 30% (Tian et al, ). The retrieval algorithms are capable of characterizing IWCs over the SR regions of midlatitude continental convective systems.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the possible reasons for the retrieval differences and their low correlation, the uncertainty of NEXRAD retrievals is analyzed first. Tian et al () found that the NEXRAD‐retrieved IWC is 20% larger than the aircraft in situ measurements; thus, it is highly probable that the NEXRAD IWPs will be roughly 20% larger than the “true” IWPs, if the in situ measurements are treated as “ground‐truth.” As mentioned in section 2.1, supercooled liquid water was observed by aircraft probes during MC3E around the −30°C level, similar to previous reports (Rosenfeld & Woodley, ). Those large amounts of supercooled liquid water may enhance NEXRAD radar reflectivity measurements and therefore result in larger IWC retrievals and overestimation of IWPs.…”
Section: Resultsmentioning
confidence: 99%
“…However, a significant amount of supercooled liquid water was observed by aircraft probes above 4 km (see Figure 2 in Wang et al, , for reference). IWC retrievals using measured radar reflectivity for ice cloud with contamination of supercooled liquid water can result in relatively large uncertainties near the melting band (Tian et al, ). Thus, in this study, IWP is calculated by integrating NEXRAD‐estimated IWC profile from 5 km to cloud top (NEXRAD radar echo top).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation